Smart Biosensor Berbasis Nanopartikel Tembaga dengan Reduktor Kulit Buah Naga sebagai Pendeteksi Formalin pada Sampel Makanan - Qomariyah, Ani; Fisabilla, Adhinda; Hanifa, Nur Lailatul; Kusuma, Okta Nata (Chemistry Department, Universitas Islam Indonesia, 2024)
Green chemistry technique was conducted for the first time to synthesize copper nanoparticles (Cu-NP) using CuSO4 as precursor and red dragon fruit peel extract as reducing agent which was then applied as formalin sensor. The extraction procedure of red dragon fruit peel was carried out by maceration technique with methanol solvent. Cu-NPs were produced through green chemistry by reduction method. Compounds in red dragon fruit peel extract reduce Cu2+ to Cu0. The successfully synthesized Cu-NPs were analyzed using FT-IR and UV-Visible Spectrophotometer. Identification of functional groups with FTIR showed a shift in wave number between pure CuSO4 precursor and Cu-NPs, indicating the interaction of functional groups. Based on 15 samples tested for formaldehyde levels, there were two samples with levels above the threshold, namely meatball 2 with an average formaldehyde level of 13.77 ± 0.25 ppm packaged without a “Halal” label and tofu 3 with a formaldehyde level of 4.18 ± 0.99 ppm packaged without a “Halal” label.